Dynamic Governance Capability Modeling in Sidomulyo Village, Jember Regency - Dina Suryawati; Hari Karyadi; Muhammad Zefri Kudus (POLITICO, 2025)
The research discusses the Digital Village program implemented by the Sidomulyo Village Government in Jember Regency. The digital village initiative is realized through the development of a digital village governance system that provides administrative services, disaster mitigation, an online marketplace, and a community complaint platform. In developing this digital governance system, the Sidomulyo Village Government collaborates with partners from the education sector, private sector, and local communities. Named "MallDesa," this digital governance system is continuously developed based on the needs of both the village government and its residents, earning recognition and awards from the district and provincial governments. The research aims to explore the Digital Village program using the dynamic governance approach proposed by Neo Boon Siong (n.d., 2007). This theoretical framework employs the dimension of capabilities as an analytical tool to examine the Digital Village program. The research methodology applied is quasi-qualitative. Data were collected through interviews and documentation, with informants selected using purposive sampling techniques. Data validity was ensured through data triangulation. Data analysis was conducted using domain analysis and taxonomic analysis models (Spradley). The findings indicate that adaptive capabilities—encompassing adaptive policy capability, village governance, collaboration, human resources, and an innovative organizational culture—serve as the core driving force behind governance dynamics